POSSESSION AND VOLITION IN THE DEVELOPMENT OF MODAL MEANINGS: A CASE-STUDY FROM SICILIAN (Journal of Contemporary Philology, 2019)
This article analyses two Sicilian modal constructions involving vuliri 'want'+ infinitive and aviri a ‘have to’+ infinitive. They are used to express modal values, both non-epistemicand  epistemic,  and futurity. Based  on Langacker's  Cognitive Gram-marassumptions, we describe the semantic network associated with each modal, as well as their semantic overlap. In addition, we describe how modal values interact with temporal-aspectual inflection.Our analysis shows that the epistemic values of vuliriare quite peripheral, while aviri ashows a high degree of polysemy, both in the non-epistemic and in the more abstract epistemic domain. The non-epistemic-to-epistemic shifts depend on the contextual coordinates: basically, on the actionality of the verb, and on the agentivity of the Trajector, therefore on the feature of Inten-tionality which has proved to be crucial in the processes here analysed. On the whole, aviri a exhibits a higher degree of grammaticalisation compared to vuliri: while the latter maintains its “verbiness”, the former appears to be a stable means of modal expression interacting with the other contextual coordinates in a rather complex way.
Keywords: Sicilian modals; cognitive grammar; subjectification; modality; future